INTERAKSI SOSIAL DALAM KESENIAN KOMPANG PADA MASYARAKAT DUSUN DELIK, BENGKALIS - Hengki Armez Hidayat; Nursyirwan Nursyirwan; Rosta Minawati (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2017)
Kompang lives together with Malay Bengkalis people that majority of them are Muslims. Kompang as an art is present in the celebration of cultural events and it becomes the part of Malay Bengkalis people’s cultural processions. In this writing, it is discussed the social interaction and Kompang existence in the people of Dusun Delik as the area of Kompang art development. This research step used the qualitative method, with the approaches of anthropology, sociology, and ethnomusicology. The technique of data collection was conducted by doing observation, interview, and documentation. Those data were triangulated and coupled into sentences together with researcher’s observation and interpretation. Research result is the existence of a reciprocal relationship and social interaction in its society. In one side, Kompang has a role in its people condition; on the other side, Kompang lives and develops together with its people’s participation. Kompang in its social form is about humans’ relations in their societal group, while its spiritual form is praises and shalawat and salam sung together with the rhythm of jawab (tamsilam) and hadi (berzanji) lyrics.Keywords: Kompang Art, Social Interaction, Dusun Delik People